Epidemiology of glomerular diseases in Kazakhstan during the period of 2014-2019: data from the Unified national electronic healthcare system - Ainur Assan; Gulnur Zhakhina; Zakira Kerimbayeva; Ikilas Moldaliyev; Dmitry Sychev; Saltanat Tuganbekova; Abduzhappar Gaipov (National Scientific Medical Center, 2024)
Brief Description: The investigation of glomerular disease prevalence is vital for comprehending chronic kidney disease development, particularly in regions like Kazakhstan and Central Asia, where confirming data is lacking. This study focuses on the epidemiology of glomerular diseases, utilizing registered cases of glomerular diseases in the national electronic health system. Research Methods: The research involves data from 31,421 patients recorded in the Unified National Electronic Healthcare System database, covering glomerular diseases with ICD-10 codes N01-N08 between 2014 and 2019. Descriptive statistics encompass demographic characteristics, all-cause mortality, prevalence and incidence rates, and comorbidities. Results: Results reveal a substantial rise in diagnosed cases from 7,756 (2014) to 30,686 (2019), with corresponding all-cause mortality increasing from 254 to 1,025. Also, new cases went up from 4,875 (2014) to 6,320 (2019). Over the period, 51% were women, 49% were men, and 67% were of Kazakh ethnicity. Russian nationality constituted 16%, and other ethnic groups comprised 17%. Diabetes mellitus emerged as the primary comorbidity, associated with 20% of cases. Conclusion: This is the first descriptive study in Central Asia scrutinizing the epidemiology of patients with glomerular diseases (ICD-10 code N01-N08) using administrative healthcare data in Kazakhstan. The findings indicate an escalation in prevalence and mortality, coupled with a gradual increase in incidence among glomerular disease patients from 2014 to 2019. The study underscores the pivotal role of diabetes mellitus as a predominant comorbidity in this context.